Integrating corporate social responsibility into efforts to realize millennium development goals: Lessons from Uganda. Issue 4 (7th October 2014) - Katamba, David; Marvin Nkiko, Cedric; Tushabomwe-Kazooba, Charles; Babiiha Mpisi, Sulayiman; Kemeza, Imelda; M.J. Wickert, Christopher
Abstract : Purpose: – The purpose of this paper is to present corporate social responsibility (CSR) as an alternative roadmap to accelerating realization of Millennium Development Goals (MDGs) in Uganda, even after 2015. Design/methodology/approach: – Using a mixed research methodology, this research documented CSR activities of 16 companies operating in Uganda. Data collection was guided by quantitative and qualitative methodologies (semi-structured interviews with CSR managers, plus non-participant observation of CSR activities and projects linked with MDGs). Triangulation was used to ensure credibility and validity of the results. For data analysis, the authors followed a three-stepwise process, which helped to develop a framework within which the collected data could be analyzed. For generalization of the findings, the authors were guided by the "adaptive theory approach". Findings: – Uganda will not realize any MDGs by 2015. However, CSR activities have the potential to contribute to a cross-section of various MDGs that are more important and relevant to Uganda when supported by the government. If this happens, realization of the MDGs is likely to be stepped up. CSR's potential contributions to the MDGs were found to be hindered by corruption and cost of doing business. Lastly, MDG 8 and MDG 3 were perceived to be too ambiguous to be integrated into company CSR interventions, and to a certain extent were perceived to be carrying political intentions which conflict with the primary business intentions of profit maximization. Practical implications: – Governments in developing countries that are still grappling with the MDGs can use this research when devising collaborations with private-sector companies. These documented CSR activities that contribute directly to specific MDGs can be factored into the priority public-private partnership arrangements. Private companies can also use these findings to frame their stakeholder engagement, especially with the government and also when setting CSR priorities that significantly contribute to sustainable development. Originality value: – This research advances the "Post-2015 MDG Development Agenda" suggested during the United Nations MDG Summit in 2010, which called for academic and innovative contributions on how MDGs can be realized even after 2015.